Fakta poligami sebagai bentuk kekerasan terhadap perempuan: Kajian lintasan tafsir dan isu gender - Wely Dozan (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2020)
This paper is strongly influenced by the fact that polygamy is a form of violence against women in the study of the trajectory of gender interpretations and issues. The focus of this research will be to analyze polygamy in the discourse of thought and gender issues are seen as an environment and have a detrimental impact on women. The jargon of tafsir scholars in understanding the text of the Koran, namely